STRATEGIC ANALYSIS AND DATA COLLECTION IN THE ILLICIT ASSETS RECOVERY (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
The article analyzes the legal and institutional architecture of strategic analysis and data collection, the initial stage of the illicit assets recovery. The research focus is on the mechanisms for financial and other supervised organizations to comply with Know Your Customer/Customer Due Diligence (KYC/CDD) requirements, identify suspicious transactions through internal controls, and submit suspicious transaction reports (STRs) in a timely manner. The international criteria are the FATF standards on CDD (Customer Due Diligence), STR (Suspicious Transaction Report), PEP (Politically Exposed Person), high-risk countries, beneficial ownership transparency, and the UNCAC rules that establish assets recovery as a fundamental principle. The problem areas are proposed to improve the quality of beneficial ownership data, early detection of nominee/nominator schemes, segmentation of offshore risks, and acceleration of information exchange.